Beyond total area protected: A new set of metrics to measure progress in building a robust protected area estate. (September 2019) - Cook, Carly N.; Valkan, Rebecca S.; McGeoch, Melodie A.
Highlights: Total area protected is a widely used but flawed measure of conservation progress. We develop a set of indicators that provide a more nuanced assessment of progress. The indicators represent elements of effective PA design and management. Our indicators reveal that most Australian PAs are small and under increasing pressure. These indicators can provide a clearer picture of how to strengthen PA networks. Abstract: With protected areas identified as the primary tool to halt the loss of biodiversity, the Convention on Biological Diversity has set targets for protected area expansion. Increasingly, concerns are being raised that target-driven growth, where targets focus largely on quantity (total area protected) rather than quality, may fail to achieve their intended biodiversity outcomes. Therefore, it is important to assess whether growth in area protected is translating into a more robust system of protected areas that better safeguard biodiversity. In this study, we propose a set of seven indicators, drawing on the body of evidence for the elements of protected area design and management associated with better biodiversity outcomes. Many of the features of effective design and management interact with one another, making it essential to use a suite of indicators and consider progress relative to trends across all of these indicators. We implemented the proposed indicators for the Australian National Reserve System, which has undergone significant growth over the past two decades. Our findings demonstrate that relying on trends in total area protected can obscure negative trends in other important indicators which suggest many protected areas in Australia are under increasing pressure. Meanwhile, the level of resourcing for management has not kept pace with increases in total area protected and has certainly not scaled with changes in pressures on protected areas. It is important that the global conservation community strive for a more nuanced set of indicators for conservation progress to identify whether growth in area protected has, or has not, translated into a more robust and effective system of protected areas. Given that most of the indicators we propose can be populated with existing data, we believe this approach could be achievable for protected areas globally.